A crucial distinctive author contact information - Culp, John E. (International journal for philosophy of religion, 2022)
A mutual relation between God and the world provides a crucial distinction between panentheism and both classical theism and pantheism. Several proposals responding to Analytical Theology's challenge to distinguish panentheism from other forms of theism are considered and found inadequate. After defining mutual relation, conceptual evidence and the frequency of descriptions of panentheism that affirm a mutual relation between God and the world provide evidence that a mutual relation is crucial to distinguishing panentheism. Finally, benefits of recognizing a mutual relation between God and the world as crucial to panentheism are described.